Software development for estimating the concentration of radioactive cesium in the skeletal muscles of cattle from blood samples. (30th September 2015) - Fukuda, Tomokazu; Hiji, Masahiro; Kino, Yasushi; Abe, Yasuyuki; Yamashiro, Hideaki; Kobayashi, Jin; Shimizu, Yoshinaka; Takahashi, Atsushi; Suzuki, Toshihiko; Chiba, Mirei; Inoue, Kazuya; Kuwahara, Yoshikazu; et al.
Abstract: The 2011 earthquake severely damaged the Fukushima Daiichi Nuclear Power Plant (FNPP), resulting in the release of large quantities of radioactive material into the environment. The deposition of these radionuclides in rice straw as livestock feed led to the circulation of contaminated beef in the market. Based on the safety concern of the consumers, a reliable method for estimating concentrations of radioactive cesium in muscle tissue is needed. In this study, we analyzed the concentrations of radioactive cesium in the blood and skeletal muscle of 88 cattle, and detected a linear correlation between them. We then developed software that can be used to estimate radioactive cesium concentrations in muscle tissue from blood samples. Distribution of this software to the livestock production field would allow us to easily identify high‐risk cattle, which would be beyond the safety regulation, before shipping out to the market. This software is planned to be released as freeware. This software would contribute to food safety, and aid the recovery of the livestock industry from the damage creacted by the 2011 Tohoku earthquake and tsunami.